Phasic stabilization of motor output after auditory and visual distractors. Issue 12 (29th September 2015) - Piitulainen, Harri; Bourguignon, Mathieu; Smeds, Eero; De Tiège, Xavier; Jousmäki, Veikko; Hari, Riitta
Abstract: To maintain steady motor output, distracting sensory stimuli need to be blocked. To study the effects of brief auditory and visual distractors on the human primary motor (M1) cortex, we monitored magnetoencephalographic (MEG) cortical rhythms, electromyogram (EMG) of finger flexors, and corticomuscular coherence (CMC) during right‐hand pinch (force 5–7% of maximum) while 1‐kHz tones and checkerboard patterns were presented for 100 ms once every 3.5–5 s. Twenty‐one subjects (out of twenty‐two) showed statistically significant ∼20‐Hz CMC. Both distractors elicited a covert startle‐like response evident in changes of force and EMG (∼50% of the background variation) but without any visible movement, followed by ∼1‐s enhancement of CMC (auditory on average by 75%, P < 0.001; visual by 33%, P < 0.05) and rolandic ∼20‐Hz rhythm (auditory by 14%, P < 0.05; visual by 11%, P < 0.01). Directional coupling of coherence from muscle to the M1 cortex (EMG→MEG) increased for ∼0.5 s at the onset of the CMC enhancement, but only after auditory distractor (by 105%; P < 0.05), likely reflecting startle‐related proprioceptive afference. The 20‐Hz enhancements occurred in the left M1 cortex and were for the auditory stimuli preceded by an early suppression (by 7%, P < 0.05). Task‐unrelated distractors modulated corticospinal coupling at ∼20 Hz. We propose that the distractors triggered covert startle‐like responses, resulting in proprioceptive afference to the cortex, and that they also transiently disengaged the subject's attention from the fine‐motor task. As a result, the corticospinal output was readjusted to keep the contraction force stable. Hum Brain Mapp 36:5168–5182, 2015 . © 2015 Wiley Periodicals, Inc.